1975
DOI: 10.1139/v75-059
|View full text |Cite
|
Sign up to set email alerts
|

A Raman Spectral Study of the Kinetics of Hydrolysis of Acetonitrile Catalyzed by Hg(II)

Abstract: Yu-KEUNG SZE and DONALD E. IRISH. Can. J. Chem. 53,427 (1975). Rarnan spectroscopy has been employed to follow the relatively slow rate of hydrolysis of acetonitrile, catalyzed by rnercury(I1). Rarnan lines at 2275 and 2305 crn-' are characteristic of CH3CN bound to HgZ+, and are distinct from lines of bulk solvent. The intensities of these new lines decrease with time. From the intensities, concentrations of bound acetonitrile, [CH3CNIB were calculated for a time span of 400 min. The data fit a second order r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Further support for a surface hydrolysis reaction may be given by the results reported for the hydrolysis of acetonitrile . A slow hydrolysis was measured under mild conditions at room temperature catalyzed by Hg 2+ with the conversion of acetonitrile to acetamide in a high yield and purity as determined by Raman spectroscopic measurements.…”
Section: Resultsmentioning
confidence: 86%
“…Further support for a surface hydrolysis reaction may be given by the results reported for the hydrolysis of acetonitrile . A slow hydrolysis was measured under mild conditions at room temperature catalyzed by Hg 2+ with the conversion of acetonitrile to acetamide in a high yield and purity as determined by Raman spectroscopic measurements.…”
Section: Resultsmentioning
confidence: 86%
“…It is interesting that the properties of Br^nsted acids in these two solvents show a parallel behavior. For example, Kolthoff and Chantooni (30) concluded that in such systems the behavior of 2-PrOH is closer to that of -BuOH than to that of 1-PrOH, even though the dielectric constant of t-BuOH (12) is much lower than those of 2-PrOH (18) and 1-PrOH (20).…”
Section: Resultsmentioning
confidence: 99%
“…All potential measurements were made within 3 h after preparation of copper(II) solutions. In the case of water-acetonitrile and water-dimethylformamide mixtures, measurements were made immediately after preparation of solutions because it is conceivable that hydrolysis of acetonitrile and dimethylformamide will be catalyzed by copper(II) ion, as it is by mercury(II) (18).…”
mentioning
confidence: 99%
“…Hydrolysis of acetonitrile (to form acetic acid) occurs under acidic conditions but is very slow. 32 Furthermore, in this system only trace amounts of water and few protons are present. Reactions between formic acid and acetonitrile might reasonably be expected to lead to a product exhibiting an NH stretching mode.…”
Section: Formic Acid-acetonitrilementioning
confidence: 95%